Pendekatan Framework STOPE untuk Mengukur Kesiapan Pengalihan PBB pada Pemerintah Kabupaten Gunungkidul - Hari Susanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
This study aims to quantify the level of readiness the local government in accepting the transfer tax on land and buildings (PBB) from the center to the regions by using a framework approach stope (strategy, technology, organization, people, environment) to analyze five major domains, 15 sub - domain (issues), and 59 sub-sub-domains (factor). The final results of this study, using a 4 point scale issued by the Centre for International Development / CID (Harvard Cyber Law). The results of the data analysis showed that the government Gunungkidul is ranked 3 (ready) on a scale of 4 to accept the transfer of the PBB. Of the five domains, the domain strategy and organization was ranked 4 (very prepared) for the transfer of the United Nations. While the technology domains, people, and environment is ranked 3 (ready) on a scale of 4 to the divert of PBB.